2021
DOI: 10.1038/s41598-021-85265-8
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of virtual reality-based training to diagnose strabismus

Abstract: To study the usefulness of virtual reality (VR)-based training for diagnosing strabismus. Fourteen residents in ophthalmology performed at least 30 VR training sessions to diagnose esotropia and exotropia. Examinations of real patients with esotropia or exotropia before and after the VR training were video-recorded and presented to a strabismus expert to assess accuracy and performance scores for measuring the deviation angle and diagnosing strabismus with anonymization. A feedback survey regarding the usefuln… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…VR and AR have been explored in many aspects in ophthalmologic and optometric fields, such as low vision [ 13 ], glaucoma [ 14 , 15 ], strabismus [ 16 , 17 ], testing binocular imbalance [ 18 , 19 ], age-related macular degeneration [ 20 ], and distance-based vision aid for blind [ 13 ]. Several studies aimed to train amblyopia based on VR technology and showed various improvement in visual acuity.…”
Section: Introductionmentioning
confidence: 99%
“…VR and AR have been explored in many aspects in ophthalmologic and optometric fields, such as low vision [ 13 ], glaucoma [ 14 , 15 ], strabismus [ 16 , 17 ], testing binocular imbalance [ 18 , 19 ], age-related macular degeneration [ 20 ], and distance-based vision aid for blind [ 13 ]. Several studies aimed to train amblyopia based on VR technology and showed various improvement in visual acuity.…”
Section: Introductionmentioning
confidence: 99%
“…Since the introduction of VR in the world of computing, it has been used for different purposes, including gaming, education, industrial applications, and medical applications. In the field of medicine, VR has been used for training medical procedures ( Tin, Hertelendy & Ciottone, 2021 ; Moon et al, 2021 ; Nambi et al, 2021 ), to evaluate sight ( Yasuda et al, 2020 ; Sabu et al, 2020 ), and in rehabilitation ( Chen, 2021 ; Laver et al, 2015 ; Tin, Hertelendy & Ciottone, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Statistical analysis was performed using SPSS Win 18.0 program, and the scores of the real and virtual fabric evaluation were compared using the t-test. The relationships between the real and virtual evaluation modes, and the difference in the image of the subjective sensation of real clothing and virtual clothing, were evaluated using Pearson correlation coefficients …”
Section: Methodsmentioning
confidence: 99%
“…The relationships between the real and virtual evaluation modes, and the difference in the image of the subjective sensation of real clothing and virtual clothing, were evaluated using Pearson correlation coefficients. 32 …”
Section: Methodsmentioning
confidence: 99%